Understanding Psychology - Woods Barbara (Hodder Arnold, 2004)
This book provides a clear introduction to the work and ideas of psychologists.Introduction, Acknowledgements, Forming Impressions of Other People, Prejudice and Discrimination, Social Influence, Attachment and Separation, Cognitive Development, Sex and Gender, The Development of Moral Behaviour, Pro-social Behaviour, Anti-social behaviour, Perception, Learning, Memory, Research Methods, Planning and Carrying Out and Writing Up an Investigation, Glossary, Further Reading, Websites, Index.